2003
DOI: 10.1074/jbc.m300554200
|View full text |Cite
|
Sign up to set email alerts
|

RASSF2 Is a Novel K-Ras-specific Effector and Potential Tumor Suppressor

Abstract: Ras proteins regulate a wide range of biological processes by interacting with a broad assortment of effector proteins. Although activated forms of Ras are frequently associated with oncogenesis, they may also provoke growth-antagonistic effects. These include senescence, cell cycle arrest, differentiation, and apoptosis. The mechanisms that underlie these growth-inhibitory activities are relatively poorly understood. Recently, two related novel Ras effectors, NORE1 and RASSF1, have been identified as mediator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
191
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(202 citation statements)
references
References 29 publications
8
191
2
1
Order By: Relevance
“…RASSF2 is a K-Ras effector with growth suppressing and pro-differentiation properties. 56 AIM2 is an IFN-inducible proapoptotic nuclear protein, which suppresses growth of mammary cells in vitro and tumors in vivo. 57 We were unable to observe changes in p21 or p27 CDKIs, but we point to another CDKI -p57Kip2-as a target in HaCat.…”
Section: Discussionmentioning
confidence: 99%
“…RASSF2 is a K-Ras effector with growth suppressing and pro-differentiation properties. 56 AIM2 is an IFN-inducible proapoptotic nuclear protein, which suppresses growth of mammary cells in vitro and tumors in vivo. 57 We were unable to observe changes in p21 or p27 CDKIs, but we point to another CDKI -p57Kip2-as a target in HaCat.…”
Section: Discussionmentioning
confidence: 99%
“…Re-expression of RASSF2A, AD037A and NORE1A also results in suppression of tumour growth in a variety of different tumour types Chen et al, 2003;Vos et al, 2003a, b;Aoyama et al, 2004;Eckfeld et al, 2004;Akino et al, 2005;Zhang et al, 2007). For several RASSF members growth suppression is enhanced by co-transfection of constitutively active Ras proteins (Vos et al, 2000(Vos et al, , 2003a or by artificially forcing membrane localization thereby facilitating interaction with Ras (Eckfeld et al, 2004). Co-immunoprecipitation experiments show that RASSF proteins bind several Ras superfamily members as Ras-guanosine triphosphate (GTP) but not Ras-GDP and that this interaction occurs between the RA domain and the effector domain of Ras proteins (Vavvas et al, 1998;Vos et al, 2000Vos et al, , 2003aKhokhlatchev et al, 2002;Ortiz-Vega et al, 2002;Eckfeld et al, 2004).…”
Section: Rassf1mentioning
confidence: 99%
“…For several RASSF members growth suppression is enhanced by co-transfection of constitutively active Ras proteins (Vos et al, 2000(Vos et al, , 2003a or by artificially forcing membrane localization thereby facilitating interaction with Ras (Eckfeld et al, 2004). Co-immunoprecipitation experiments show that RASSF proteins bind several Ras superfamily members as Ras-guanosine triphosphate (GTP) but not Ras-GDP and that this interaction occurs between the RA domain and the effector domain of Ras proteins (Vavvas et al, 1998;Vos et al, 2000Vos et al, , 2003aKhokhlatchev et al, 2002;Ortiz-Vega et al, 2002;Eckfeld et al, 2004). In the case of RASSF1A association with Ras may occur indirectly through heterodimerization with NORE1A or the scaffold protein CNK1 (Ortiz-Vega et al, 2002;Rabizadeh et al, 2004).…”
Section: Rassf1mentioning
confidence: 99%
“…To date, RASSF1 -8 have been identified (Falvella et al, 2006), and RASSF1,2,4,5 have been shown to mediate Ras-dependent cell cycle arrest and apoptotic death (Vos et al, 2003). Moreover, these proteins are all frequently downregulated during tumour development by promoter CpG island methylation (Dammann et al, 2003;Vos et al, 2003;Aoyama et al, 2004;Eckfeld et al, 2004).…”
mentioning
confidence: 99%